2000
DOI: 10.1038/sj.ejhg.5200532
|View full text |Cite
|
Sign up to set email alerts
|

Psychological consequences of predictive genetic testing: a systematic review

Abstract: The aim of this systematic literature review is to describe the psychological consequences of predictive genetic testing. Five databases were searched for studies using standardised outcome measures and statistical comparison of groups. Studies were selected and coded by two independent researchers. From 899 abstracts, 15 papers, describing 11 data sets, met the selection criteria for the review. The studies were of predictive genetic testing for Huntington's disease, hereditary breast and ovarian cancer, fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
263
3
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(292 citation statements)
references
References 41 publications
17
263
3
9
Order By: Relevance
“…The psychological impact on asymptomatic gene carriers has been extensively studied in familial cancer and neurological disease patients, and likewise no significant effect on emotional well-being or HR-QoL has been reported to date. [8][9][10] Adaptation to the shift in health status, as well as the advantages of a gain in knowledge and more accurate risk perception have all been suggested to account for this lack of psychological harm following a positive predictive result, and this is well described in the literature. 22,23 Of note, both proband groups (Groups 1 and 2) showed low HR-QoL scores, reflecting the fact they have clinical evidence of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The psychological impact on asymptomatic gene carriers has been extensively studied in familial cancer and neurological disease patients, and likewise no significant effect on emotional well-being or HR-QoL has been reported to date. [8][9][10] Adaptation to the shift in health status, as well as the advantages of a gain in knowledge and more accurate risk perception have all been suggested to account for this lack of psychological harm following a positive predictive result, and this is well described in the literature. 22,23 Of note, both proband groups (Groups 1 and 2) showed low HR-QoL scores, reflecting the fact they have clinical evidence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…7 Predictive genetic testing of asymptomatic individuals at risk for disease can elicit a number of psychosocial responses, and understanding these has been an important research focus. [8][9][10] Fear and concern that predictive genetic testing will have a negative impact on psychological state is largely unfounded based on studies carried out in cancer and neurologic genetic diseases. [8][9][10] In cardiac genetics, the data are limited with only a small number of studies investigating the impact of genetic testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadstock et al, 2000). Qualitative studies have, however, brought into relief significant differences in how genetic risks are emotionally experienced.…”
Section: Perceptions Of Genetic Riskmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Some studies have demonstrated positive attitudes and support for genetic testing in RD [15][16][17] but the potentially negative psychological consequences associated with predictive testing underline the need for counselling protocols to support families. 15 A strong motivating factor to seek genetic testing for RD has been reported to be the opportunity to access novel therapies 16 but, while such treatments remain unavailable for the vast majority of inherited retinal disorders, testing benefits are likely to centre on improving diagnosis, understanding of inheritance pattern and prognosis.…”
Section: Introductionmentioning
confidence: 99%